2007
DOI: 10.1038/nature05656
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear cytokine-activated IKKα controls prostate cancer metastasis by repressing Maspin

Abstract: Inflammation enhances tumour promotion through NF-kappaB-dependent mechanisms. NF-kappaB was also proposed to promote metastatogenesis through epithelial-mesenchymal transition. Yet a mechanistic link between inflammation and metastasis is missing. We identified a role for IkappaB kinase alpha (IKKalpha), activated by receptor activator of NF-kappaB (RANK/TNFRSF11A), in mammary epithelial proliferation during pregnancy. Owing to similarities between mammary and prostate epithelia, we examined IKKalpha involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
353
3
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(380 citation statements)
references
References 28 publications
15
353
3
9
Order By: Relevance
“…5 In addition to its cytoplasmic functions where it controls the activation of both classical and alternative NF-κB pathways, 6,[9][10][11][12] IKKα can function as a nuclear protein kinase, [33][34][35] and nuclear IKKα plays important roles in prostate cancer progression and metastasis. 13,14 In the present study we have shown that IKKα controls the biogenesis of a group of miRNA, including miR-196a. Phosphorylation of IKKα at 23 T site promotes the association of IKKα with pri-miRNAs, where MiR-196a has two forms: miR-196a1 and miR-196a2.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…5 In addition to its cytoplasmic functions where it controls the activation of both classical and alternative NF-κB pathways, 6,[9][10][11][12] IKKα can function as a nuclear protein kinase, [33][34][35] and nuclear IKKα plays important roles in prostate cancer progression and metastasis. 13,14 In the present study we have shown that IKKα controls the biogenesis of a group of miRNA, including miR-196a. Phosphorylation of IKKα at 23 T site promotes the association of IKKα with pri-miRNAs, where MiR-196a has two forms: miR-196a1 and miR-196a2.…”
Section: Discussionmentioning
confidence: 51%
“…Recently, we found that IKKα can be translocated into the nucleus and nuclear IKKα plays important roles in prostate cancer progression and metastasis. 13,14 MicroRNAs (miRNAs) regulate gene expression through suppression of translation and decay of target mRNAs, and are involved in diverse physiological and pathological processes. The primary transcripts of miRNA (pri-miRNA) are cleaved into precursor miRNA (pre-miRNA) by nuclear Drosha, and further processed to mature miRNAs by cytoplasmic Dicer1 in mammalian miRNA biogenesis.…”
mentioning
confidence: 99%
“…IKK-dependent but NF-κB transcription-independent function is also involved in the control of metastasis. It has been shown that genetic inhibition of IKKα kinase activity promotes Maspin expression and reduces metastatic potential of the cancer cells (Luo et al, 2007). Moreover, NF-κB is involved in angiogenesis by controlling key angiogenesis factors such as VEGF, IL-6, MCP-1 and MMPs (Schmidt et al, 2007).…”
Section: Function Of Stat3 In Inflammation and Cancermentioning
confidence: 99%
“…[34][35][36][37] Similarly, IkB kinase-a-activation reduces the infiltration of RANK ligand-expressing inflammatory cells and is associated with metastasis of prostate cancer in mice. 38 These observations suggest a combined role of gene, environment (macro and micro) and immunity in the development of prostate cancer.…”
Section: Hoop Of Gene Environment and Immune Systemmentioning
confidence: 97%